2022
DOI: 10.1007/s12602-022-09985-7
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Probiotics, Prebiotics, Synbiotics, and Postbiotics in Oral Cancer Management

Abstract: Oral carcinogenesis is preceded by oral diseases associated with inflammation such as periodontitis and oral candidiasis, which are contributed by chronic alcoholism, smoking, poor oral hygiene, and microbial infections. Dysbiosis is an imbalance of microbial composition due to oral infection, which has been reported to contribute to oral carcinogenesis. Therefore, in this review, we summarised the role of probiotics, prebiotics, synbiotics, and postbiotics in promoting a balanced oral microbiome, which may pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Moreover, these practices have the potential to improve treatment-related dysbiosis in other parts of the alimentary canal: the oral cavity, for example. 129 135 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these practices have the potential to improve treatment-related dysbiosis in other parts of the alimentary canal: the oral cavity, for example. 129 135 …”
Section: Discussionmentioning
confidence: 99%
“…As a result, postbiotics can be presented as potential treatments for diarrhea that are free from major adverse effects. Salmonella induced inflammatory bowel disease (IBD) was demonstrated to be protected from postbiotic Lactobacillus paracasei ( B21060 ) (Mohd Fuad et al, 2022).…”
Section: The Impact Of Postbiotics In Immunomodulationmentioning
confidence: 99%
“…In the meantime, the word symbiotics were collected to elucidate the probiotics and prebiotics relationship that assists the host by promoting microbial colonization and survival in the gut (Vrese & Schrezenmeir, 2008). Additionally, a study revealed that the use of prebiotics, probiotics, and synbiotics (a combination of prebiotics and probiotics) could influence the yields of chemical messengers (hormone levels and neurotransmitters) and inflammatory components, interfering with the eating plan which leads to obesity (Mohd Fuad et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have also highlighted the use of synbiotics in human cancer treatment (Rafter et al, 2007;Fotiadis et al, 2008;Mego et al, 2013;Scott et al, 2018;Alam et al, 2022;Fuad et al, 2022), with studies conducted by Gibson and Roberfroid (2008), Beski and Al-Sardary (2015), Kvakova et al (2021) indicating that synbiotics better protected consumers from carcinogenic compounds when compared to probiotics and prebiotics used separately.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%